Non-invasive prenatal testing (NIPT): a call for change in reporting practices - Wilson, Samuel; Balayla, Jacques (McGill Journal of Medicine, 2024)
The use of non-invasive prenatal testing (NIPT) technology has revolutionized the practice of prenatal screening. The assay’s validity and reliability have been demonstrated in both low- and high-risk pregnancies. Despite its excellent screening parameters, its reliability is often overestimated due to confusing and incorrect terminology that appears in private NIPT reports. Herein, we provide a brief explanation of the potential implications at two different levels: patient and provider. We conclude with a call to redesign the way information is presented on NIPT reports to avoid stressing patients, enhance transparency in clinical counselling, and perhaps most critically, to prevent medical decisions that may not be warranted solely based on the NIPT results.